(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
This paper analyzes the results of application and protection of the right of access to information on climate change achieved thus far. The paper aims to point out the basis of the legal nature of information on climate change in international law and environmental acquis. It determines if the legal framework regulating the right of access to environmental information in Serbia can be applied to access to information on climate change. The final section suggests possible means to overcome the shortcomings found in domestic and comparative law.